Biomonitoring of surface water quality in Africa: Contamination levels by chemical pollutants, including emerging pharmaceutical compounds and heavy metals, and the use of biomarkers – a literature review - Amadou, Afoussatou; Kelome, Nelly; Dougnon, Victorien Tamègnon (VertigO)

(untitled) (Université du Québec à Montréal et Éditions en environnement VertigO, 2025)
Chemical pollution of surface waters represents a major challenge in Africa, particularly in urban and industrialized areas. The use of biomarkers to monitor this pollution appears to be an effective approach for assessing water quality and its impacts on aquatic ecosystems. This literature review aims to enhance knowledge on the application of biomarkers in monitoring chemical pollutants, particularly emerging pharmaceutical compounds (EPCs) and heavy metals in Africa. An analysis of 50 scientific articles published between 2010 and 2025 was conducted. The results show that biomarkers can detect the effects of chemical pollutants on aquatic organisms. An increase in enzymatic activity was observed in fish exposed to contaminants, reflecting a biological response to chemical stress. Furthermore, oxidative stress biomarkers prove particularly useful for assessing the impact of pollution by measuring free radicals and antioxidants in fish tissues. The integration of biomarkers into chemical pollution monitoring in Africa is a powerful tool for assessing water quality and the impact of human activities on aquatic ecosystems. This data provides a solid foundation for guiding future research and strengthening water quality management policies at the continental level.